156k views
5 votes
If k(x) = 2x³ - 3√x then k (9) is

User Clavin
by
6.0k points

1 Answer

3 votes

If they ask you for k (9), what you should do is replace at x = 9 in the function k (x) that they give you. Then


\begin{gathered} k(x)=2x^3-3\sqrt[]{x} \\ k(9)=2(9)^3-3\sqrt[]{9} \\ k(9)=2\cdot729-3\cdot3 \\ k(9)=1458-9 \\ k(9)=1449 \end{gathered}

Therefore, if k(x) = 2x³ - 3√x then k (9) is​ 1449.

User MEGHA RAMOLIYA
by
5.2k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.